A Case Study Of "Maxis" Celebrity Endorsement - Serpoosh, Majid (2006)
The objective of this thesis is to gain a better understanding of how celebrities are used as endorsers in advertising. To achieve this purpose four research questions are stated, why companies choose celebrity endorsement as a promotion strategy, how companies select their endorsers, how companies address the investment return on celebrity endorsement and how campanies handle the risks of using a celebrity endorser in their advertising.